Analisis Pengaruh Jumlah Angkatan Kerja dan Indeks Pembangunan Manusia terhadap Tingkat Kemiskinan dan Tingkat Pengangguran - Nur Hayati; Rizki Maulana; Paradiva BR. Ginting; Asnidar Asnidar; Ahmad Rida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to determine the effect of the human development index and economic growth on unemployment and poverty in Aceh. This research uses secondary data with a time series of 2013-2022 with the scope of Jogjakarta province. This research model uses a path analysis model using the Eviews application. The results of this research show that the number of labor force directly has a positive and insignificant effect on the level of poverty. The human development index directly has a negative and significant effect on the poverty level The number of labor force directly has a negative and significant effect on the unemployment rate. The human development index directly has a positive and significant effect on unemployment. The poverty level directly has a positive and insignificant effect on the unemployment rate. Indirectly, the number of labor force has a negative and insignificant effect on unemployment through poverty. Indirectly, the human development index has a negative and insignificant effect on unemployment through poverty.